(untitled) (Razão e Fé, 2024)
The purpose of this text is to outline the historical development of the founding of the Philosophy course at the Catholic University of Pelotas, which turned 70 in 2023. This idea came from the dream of Dom Antônio Zattera, because it was urgent and necessary to create a Catholic University in Pelotas and higher education courses throughout the diocese. This gave birth to law courses in Bagé and Rio Grande, business courses in São Gabriel and Camaquã, and a history course in Jaguarão. It was essential to have a strong, critical education that made room for teaching that also allowed Christian evangelization to be understood and accepted from a critical viewpoint. This is how the University’s Philosophy, Science and Letters course was born in 1953.